Simulation of spray direct injection for compressed air energy storage. (25th February 2016) - Qin, C.; Loth, E.
Highlights: Novel CAES can help provide levelized wind energy power output with high efficiency. Water spray was employed during compression to promote heat and mass transfer. Multi-phase CFD is implemented using a spray discharge at various mass loadings. Injected mass loading of 1.6 yielded efficiency as high as 93% in compression cycle. Abstract: Integrating Compressed Air Energy Storage (CAES) to a variable and unsteady energy source can help provide a levelized power output. This is particularly attractive for off-shore wind turbines integrated with the energy storage that has high efficiency. Such efficiency is possible if the compression portion can be isothermal, and a novel approach has been developed to achieve this by employing water spray during compression to promote heat transfer. This concept has been previously investigated with one-dimensional simulations that indicated spray cooling with droplet heat transfer over a large total surface area allows high-efficiency compression. However, the actual application is more complicated, and therefore the present study examines this concept with detailed two-dimensional unsteady flow simulations. In particular, multi-phase computational fluid dynamics is implemented in an axisymmetric domain to investigate compression in a cylinder for first-stage and second-stage compression using a spray discharge within the cylinder at various mass loadings. The spray is based on a single pressure-swirl nozzle directed along the centerline and operating at the maximum liquid mass flux possible while retaining a mean droplet diameter of no more than 30 µm. The two-dimensional simulations uncovered flow characteristics such as vortex formation for the air-flow near the cylinder head and strong spatial variations in droplet size and concentration. Despite these effects, the overall two-dimensional efficiency was similar to that of one-dimensional predictions. The results also indicated that a single pressure-swirl nozzle injection resulted in an injected mass loading of 1.6 and yielded efficiency as high as 93% for a first-stage compression cycle. However, a second-stage compression cycle (with an intake pressure of 10 bar) using this same single nozzle resulted in reduced overall work efficiency indicating that a multi-nozzle configuration should be considered.